EFFECT OF POLYETHERSULFONE COMPARED TO CELULLOSE DIACETATE DIALYZER MEMBRANE ON SERUM INTERLEUKIN-6 AND C-REACTIVE PROTEIN LEVES IN HEMODIALYSIS - Raka Widiana, I Gde (journal of internal medicine; Vol. 9, No. 2 Mei 2008)
Synthetic dialyzer membrane is considered to have greater biocompatibility properties than cellulose based dialyzer membrane. This study is aiming to determine whether the use of polyethersulfone synthetic dialyzer (PES) membrane produce lower inflammatory (IL-6 and CRP) response compared to celullose diacetate (CDA). Study samples were selected consecutively from all kidney failure patients who were undergoing routine HD at HD centers in Denpasar Mayoralty. Thirty HD patients consisted of 15 with PES (11 males and 4 females, aged 45 ±10 years) and 15 patients with CDA (8 males and 7 females, aged 48 ±13 years) were included in this study. A significant increase of plasma IL-6 per 1000 monocytes (Z=-4.103, p=0.003), from18.56±21.00 pg/dl before HD to 56.00±105.41 pg/dl after HD among two groups was found. When the increase of plasma IL-6 per 1000 monocytes during hemodialysis was compared bewteen the two groups, a significant higher increase of plasma IL-6 per 1000 monocytes in CDA group compared to PES group (71.47±142.51 pg/dl versus 3.38±4.46 pg/dl, Z=-2.883, p=0.003). There was no significant increase of plasma hs-CRP levels before-after HD among both groups. Also, there was no significant difference of plasma hs-CRP changes during HD between the two groups. Using multivariate ANCOVA, a consistent effect between the two membrane (F=18.401, p=0.000) on logistic transformed of plasma IL-6 per 1000 monocytes changes. However, this effect was not significant (F=1.937, p=0.176) on logistic transformed of plasma hs-CRP changes. It was found that plasma levels of pre HD albumin related to logistic transformed of plasma IL-6 per1000 monocytes (F=5.610, p=0.026), however, there were no relationship between HD factor (KT/V) and HD age (months), with logistic transformed of plasma IL-6 per 1000 monocytes changes. Increament of plasma IL-6 levels per 1000 monocytes during HD is smaller, however, changes of plasma hs-CRP levels during HD is similar among HD patients with PES than CDA membrane. In addition, plasma levels of pre HD albumin may affect plasma IL-6 changes during HD.
Keywords: polyethersulfone, celullose diacetate dialyzer membrane, interleukin-6, hs-CRP, hemodialysis